2019
DOI: 10.1121/1.5099163
|View full text |Cite
|
Sign up to set email alerts
|

Relation of second formant trajectories to tongue kinematics

Abstract: In this study, the relationship between the acoustic and articulatory kinematic domains of speech was examined among nine neurologically healthy female speakers using two derived relationships between tongue kinematics and F2 measurements: (1) second formant frequency (F2) extent to lingual displacement and (2) F2 slope to lingual speed. Additionally, the relationships between these paired parameters were examined within conversational, more clear, and less clear speaking modes. In general, the findings of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 23 publications
1
13
0
1
Order By: Relevance
“…Thus, F2 extent during this transition provides an index of the distinctiveness between the initial and final sounds of the diphthong, and relates to the clarity with which the diphthong is perceived. 41,42 In studies of adult speakers, F2 slope has been shown to correlate with kinematic measures of lingual speed in both healthy adults and speakers with dysarthria 8,36,43 and F2 extent has been shown to correlate with tongue displacement, 43 suggesting moderate-to-strong relations between these articulatory and acoustic parameters. Less is known about the strength of these relations in children; however, given the nonlinear changes in formants and the refinement of articulatory movements throughout childhood and adolescence, it is possible that articulatory-acoustic relations in children could differ from adults.…”
Section: B Articulatory-acoustic Relationsmentioning
confidence: 98%
See 2 more Smart Citations
“…Thus, F2 extent during this transition provides an index of the distinctiveness between the initial and final sounds of the diphthong, and relates to the clarity with which the diphthong is perceived. 41,42 In studies of adult speakers, F2 slope has been shown to correlate with kinematic measures of lingual speed in both healthy adults and speakers with dysarthria 8,36,43 and F2 extent has been shown to correlate with tongue displacement, 43 suggesting moderate-to-strong relations between these articulatory and acoustic parameters. Less is known about the strength of these relations in children; however, given the nonlinear changes in formants and the refinement of articulatory movements throughout childhood and adolescence, it is possible that articulatory-acoustic relations in children could differ from adults.…”
Section: B Articulatory-acoustic Relationsmentioning
confidence: 98%
“…34,35 Prior work has shown variability in the strength of articulatory-acoustic relations in adult speakers with and without motor speech disorders. 2,8,[36][37][38] Second formant (F2) trajectories are of particular interest because F2 is sensitive to changes in tongue movement, and the extent and slope of F2 trajectories relate to speech intelligibility for speakers with dysarthria. 12,39,40 F2 trajectories are often studied in the context of diphthongs, which involve large F2 transitions between the beginning and end of the vowel.…”
Section: B Articulatory-acoustic Relationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The reference sensors can alternatively be prepared and placed on a pair of goggles, on the frame of a pair of plastic glasses, or on a headband (e.g., Ji, Berry, & Johnson, 2013;Mefferd, 2019;Thompson & Kim, 2019;Kearney et al, 2018). The Appendix shows additional information regarding individual researchers' strategies to place reference sensors.…”
Section: Preparation and Adhesionmentioning
confidence: 99%
“…It is a quantitative acoustic measurement based on connected speech (word or sentence level). The F2 slope changes almost in response to the back and forth movements of the tongue [ 15 ], and frequency trajectories, such as diphthongs, move up and down relatively rapidly. Therefore, the F2 slope is speculated to reflect the movement speed of the tongue during articulation.…”
Section: Introductionmentioning
confidence: 99%